Aggressive squamous cell carcinoma of the cranium of a dog - Łojszczyk, Anna (BMC Vet Res, 2021)
BACKGROUND: The authors report a case of keratinized squamous cell carcinoma (SCC) in a 14-year-old dog with extensive cranial bone invasion. To our knowledge, this is the first description of such a case of cranial keratinized SCC with aggressive generalized osteolysis described in a dog. CASE PRESENTATION: The 14-year-old dog was referred for radiological examination with suspicion of head trauma with clinical signs of head deformation, exophthalmos and nasal discharge. The skull radiographs showed a large osteolytic defect of the frontal bone and parietal bone in the region of the external sagittal crest. Findings from the skull CT scan included generalized osteolysis in the region of parietal bone, frontal bones, maxilla on the right side and the nasal bone including the dorsal nasal concha. In the area of bone loss, new soft tissue formation with multifocal foci of mineralization was visible. The ultrasound examination revealed hypoechogenic changes with hyperechoic foci consistent with mineralization and poor vascularization. The brain and ocular structures were without visible changes. Fine needle aspiration cytology (FNAC) was performed, and squamous cell carcinoma was suspected. After 3 months, the re-presented to the clinic. The dog became progressively listless, his appetite was decreased, and he became acutely blind. Follow-up skull CT scan revealed significant osteolysis, which affected a significant aspect of the cranium. All bone defects had been replaced by new 3.5 cm-thick soft tissue formations with multifocal small 1–2 mm areas of mineralization. There was no evidence of metastasis. Histological examination confirmed the suspicion of squamous cell carcinoma. CONCLUSIONS: This paper is the first report of cranial SCC in a dog causing extensive bone osteolysis. The lesions in this dog originated from the frontal and parietal bones including frontal sinuses. There are variants of tumors that arise from squamous epithelium or resemble SCC in the skull. These examples include adenosquamous carcinoma and proliferating trichilemmal tumours. In addition, there is possible malignant transformation caused by papilloma viruses. In the veterinary literature, there is only one similar description of adenosquamous carcinoma in a cat with similar clinical manifestations. It is justified to suspect a process of neoplastic epithelial origin in all cases of aggressive and extensive skull bone lysis. This issue should be subject to further investigation.